Fufang Zhenzhu Tiaozhi capsule attenuates renal damage by restoring Th17/Treg balance in diabetic db/db mice - Yiqi YANG; Haibo TAN; Xiaoyu ZHANG; Minyi HUANG; Weijian BEI; Jiao GUO (KeAi Communications Co., Ltd., 2022)
Objective: To explore the renal protection effect and mechanism of Fufang Zhenzhu Tiaozhi capsule (FTZ) in diabetic db/db mice in vivo and in vitro. Methods: Male db/m mice were considered as control group, and male db/db mice were considered as diabetic kidney disease (DKD) group, which were administered with different doses of FTZ (FTZ-L, 1 g•kg-1•d-1; FTZ-H, 2 g•kg-1•d-1) and losartan (positive control, 30 mg•kg-1•d-1) treatment for 12 weeks respectively, and then all mice were sacrificed. The high glucose-induced Jurkat T cell was used to evaluate the immune regulatory effect of FTZ in vitro. The renal pathological change was evaluated by H&E method. The levels of serum creatinine (Scr), proteinuria, and urinary albumin-to-creatinine ratio (UACR) were detected by biochemical parameter test kits. The expression levels of fibronectin and collagen IV were detected by immunofluorescence (IF) and immunohistochemistry (IHC). The inflammation factors including TNF-α, TGF-β, IL-6, IL-8, and IL-10 were detected by ELISA kits. The protein expression levels of IL-17A, RORγt, Foxp3, p-NF-κB, p-IκB, NF-κB, and IκB were detected by western blot. The percentage of T helper 17 (Th17) cells and regulatory T (Treg) cells were measured by flow cytometry. Results: FTZ could significantly alleviate the renal pathological changes and decrease the levels of renal function parameters including Scr, proteinuria, UACR levels, and attenuate the renal inflammation injury by reducing the inflammatory cells infiltration and cytokines (TNF-α, TGF-β, IL-6, and IL-8) secretion, as well as inhibit NF-κB signaling pathway activation and restore the Th17/Treg balance in diabetic db/db mice. Furthermore, FTZ treatment could also decrease the protein levels of RORγt and IL-17A in high glucose-induced Jurkat T cells. Conclusion: FTZ exerted protective effects on the kidney in diabetic db/db mice, whose mechanism might be related to regulating the Th17/Treg balance and inhibiting NF-κB signaling pathway.